Peran Keterikatan Merek Media Sosial Terhadap Loyalitas Merek Melalui Kepercayaan Merek Pada Produk Skincare Skintific - Rizki Febiamalia, Tika; Anindita Hayuningtias , Kristina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
Social media is increasingly finding a place in all aspects of our lives. Social media and digital marketing allow companies to achieve their marketing goals at a relatively low cost. This study aims to determine and analyze the role of social media brand attachment on brand loyalty through brand trust in skintific skincare products. This study uses a quantitative method that collects 100 respondents by distributing questionnaires. This study uses a quantitative approach using purposive sampling techniques. Data analysis techniques use SEM PLS. Based on the results of the tests carried out, it shows that the social media brand attachment variable has a positive and significant effect through brand trust, brand trust has a positive and significant effect on brand loyalty. And the social media brand attachment variable has a positive and significant effect on brand loyalty. Consumer engagement to brands on social media can increase trust and loyalty to brands, because it builds emotional relationships, increases credibility and encourages consumers to remain loyal and recommend the brand. Companies need to pay serious attention to digital marketing strategies, especially in building social media brand attachment